Fluoride pollutants removal from industrial wastewater - G. El Diwani (Bulletin of the National Research Centre, 2022)
Abstract Background The main object of the present study is the industrial wastewater effluent treatment resulting from a solar cell manufacturing process, which is a Joint Egyptian Chinese Renewable Energy laboratory, in Sohag Governorate. Fluoric and hydrochloric acids are the main pollutants causing a pH of 1 to 3. The effluent is neutralized by the addition of both potassium hydroxide and calcium hydroxide to permit the precipitation of the resulting sparingly soluble calcium fluoride. The chlorides are partially precipitated as calcium chloride, and the further addition of hydrated aluminum sulfate is used to precipitate the remaining extra chloride as an insoluble complex to reach the allowable chloride concentration in the treated effluent. Set of experiments at bench and pilot scales were run to achieve the optimum conditions for defluorination and dichlorination taking into consideration not exceeding the allowable ranges of pollutants as soluble salts in the final effluent. Results Experimental results showed that the performance of a pilot scale was satisfactory in fluorides, chlorides, and dissolved solids by 97.64, 78.85, and 79.4% removal, respectively. Based on these results a full-scale industrial treatment unit was designed for construction and operation as a treatment unit for industrial wastewater contaminated with fluorides as main pollutant. Conclusions The recommended treatment procedure succeeded in the removal of fluorides and chlorides as main contaminants in the effluent which permit the use of treated water in the irrigation of non-edible plants, according to Egyptian Code No. (501/2015).